Diarrhoea‐causing enteric protist species in intensively and extensively raised pigs (Sus scrofa domesticus) in Southern Spain. Part I: Prevalence and genetic diversity. Issue 4 (24th November 2021) - Dashti, Alejandro; Rivero‐Juárez, Antonio; Santín, Mónica; George, Nadja S.; Köster, Pamela C.; López‐López, Pedro; Risalde, María A; García‐Bocanegra, Ignacio; Gómez‐Villamandos, Jose Carlos; Caballero‐Gómez, Javier; Frías, Mario; Bailo, Begoña; et al.
Abstract: Numerous protist species are shared between humans and pigs. Among those, Giardia duodenalis, Cryptosporidium spp. and Balantioides coli have a clear public and animal health significance. For others such as Enterocytozoon bieneusi and Blastocysti s sp., their impact on animal health has not been fully established. Little information is currently available on the molecular diversity of these protists in swine populations. To fill this gap, we molecularly assessed G. duodenalis, Cryptosporidium spp., B. coli, Blastocystis sp. and E. bieneusi in faecal samples from Iberian and Large White pigs raised under different (intensive and/or extensive) management systems in southern Spain. A total of 151 extensively raised Iberian pigs, 140 intensively raised Iberian pigs, and 184 intensively raised Large White pigs were investigated. Blastocystis sp. was the agent most prevalently found (47.8%), followed by B. coli (45.5%), G. duodenalis (10.7%), E. bieneusi (6.9%), and Cryptosporidium spp. (5.5%). Blastocystis sp. was significantly less prevalent in intensively raised Iberian pigs (22.9%) than in their extensively raised counterparts (51.0%) or in intensively raised Large White pigs (64.1%). A significantly higher prevalence was found for G. duodenalis, Cryptosporidium spp., and E. bieneusi in Large White pigs than Iberian pigs. Balantioides coli was similarly distributed (40.0–51.1%) in all three investigated swine populations. Sequence analyses revealed the presence of G. duodenalis assemblage E, two Cryptosporidium species ( Cryptosporidium scrofarum and Cryptosporidium suis ), B. coli (genotypes A and B), Blastocystis sp. (ST1, ST3, and ST5), and E. bieneusi (EbpA, EbpC, EbpD, O, and a novel genotype named PigSpEb2). Novel genotype PigSpEb2 was found alone or in combination with EbpA. Data suggest a widespread exposure to protist enteroparasites in domestic pig populations irrespectively of breed and raising management system. Many of the species/genotypes identified have a zoonotic potential and might represent a public health concern.